Intervensi Brief Behavioral Treatment of Insomnia Secara Daring Untuk Menurunkan Tingkat Gangguan Insomnia Klinis - Irfan Sukma Ardiatama; Rahma Widyana; Kondang Budiyani (Universitas Islam Indonesia, 2021)
This research was aimed to find out the effect of brief behavioral treatment to decrease insomnia disorder level, which was adapted from BBTI (Brief Behavioral Treatment of Insomnia) and carried out as online intervention. The research subject were 4 adults within 20 – 29 years old age range, with moderate clinical insomnia measured with ISI (Insomnia Severity Index) in which already adapted in Indonesian language by Jaya (2012). The research design used was one group pretest-posttest with analysis within group, in which all subjects received the same treatment, and the measurement were based from the change in insomnia severity levels by each subjects. The data analysis method in this research were non-parametric tests of Wilcoxon Signed Rank Test. The result of Wilcoxon Signed Rank Test indicates that the brief behavioral treatment in this research effectively decreased insomnia level as sleep disorder in each subjects.